MULTIFUNCTION OF LAYERED AND POROUS MATERIALS - Karna Wijaya (Indonesian Journal of Chemistry, 2002)
In this review, two sort of materials i.e layered and porous materias which were studied by the author and coworkers intensively and extensively  will be described. These materials generally can be classified into two groups, namely layered organic and inorganic materials and porous organic and inorganic materials. To the materials which classified in the first group, it will be discussed the syntheses, characterization and application of layered organic materials of imidazolium-dimesylamidate and of layered inorganic materials of montmorillonite. For the second group, as examples we will analogically describe the syntheses, characterization and application of 2,6-dimethylpyridinium-di(methanesulfonyl)amidate porous organic material and zeolite and pillared clay porous inorganic materials.